THE EFFECT OF DIFFERENT A LURE ON LONGLINE CATCHES IN THE LAKE VILLAGE OF PONGKAI ISTIQOMAH SUBDISTRICT XIII KOTO KAMPAR DISTRISCT KAMPAR PROVINCE RIAU - Ahmad Jumadil TsaniSyam; Pareng Rengi; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted on 19-29 July 2017 in the Pongkai Istiqomah Village Lake District XIII Koto Kampar Kampar Regency, Riau Province. The purpose of this study was to determine the effect of different types of lure on the catch of longline fishing gear. This type of lure is to be used in the waters of the Pongkai Istiqomah Village Lake District XIII Koto Kampar, Kampar Regency, Riau Province. The feed factor is very influential on the catches. The feed used (both type and size) must be able to provide stimulation for fish and other catches to approach and eat the bait (Boesono et al. 2012). The result of catches using paweh lure (Osteochilus hasselti) (Feed 1) is as many as 22 tails. The most catches using paweh lure (Osteochilus hasselti) (Feed 2) are on the 6 day of many as 4 tails. While the least results are on days 1 and 7 with the result that no fish are caught. The catches using Siban fish lure(Cyclocheilichthys apogon) (Lure 2) were as many as 14 tails. The catch using this bait has an average catch of 2 tails. While the catch using the catfish (Peristolepis grooti) lure (Lure 3) is 7 tails. The most catches are on the 8 day, which is as much as 2 tails. The types of catches during the research is Baung, Toman and Pufferfish.Keyword: lure, longline, longline catches